Antioxidant Properties of The Ethyl Acetate Extract of Endophytic Fungus Penicillium Citrinum from Kalanchoe Millotii Stem Through Secondary Metabolites - Isma Nur Aisyiyah; Heni Rahmawati; Dewi Meliati Agustini; Sari Purbaya; Lilis Siti Aisyah; Yenny Febriani Yun (Department of Chemistry, Faculty of Science and Technology, UIN Sunan Gunung Djati Bandung, 2023)
Kalanchoe, as Cocor Bebek, is a genus of plants that is often used in traditional medicine because it has various biological activities, one of which is as an antioxidant. The development of research was carried out on the secondary metabolites compounds of endophytic fungi from the stem of K. millotii as the Cocor Bebek species. Endophytic fungi are microorganisms that live in plant tissues, generally producing secondary metabolites that have bioactivities such as anticancer, antioxidant, and antibacterial. One of the endophytic fungi isolated from the stem of K. millotii was identified as Penicillium citrinum. The potential antioxidant activity of the secondary metabolites contained in the ethyl acetate extract of the endophytic fungus P. citrinum is interesting to study. The sample extract was extracted using non-polar, semi-polar, and polar solvents. The ethyl acetate extract was separated and purified by various chromatographic methods to obtain 8 mg compound 1, as a yellow solid. The chemical structure was determined by spectroscopic methods. Based on spectrum analysis of 1D-NMR, 2D-NMR, FTIR, and UV-Vis, compound 1 was identified as 4-(2-ethylbutoxy)-3,5-dimethoxybenzaldehyde. Antioxidant activity testing of ethyl acetate extract and compound 1 was carried out using the DPPH (2,2-diphenyl-1-pikrilhidrazyl) method. The test results on the extract showed weak activity with an IC50 value of 401.01 ppm while compound 1 showed moderate activity with an IC50 value of 221.41 ppm